Stereotypes, prejudice and social exclusion in a multiethnic country: the Peruvian case - Espinosa, Agustín (2007)
Based in a sample of middle class participants from Lima city (n = 81), intergroup relations’ dynamic is analyzed. Considering the stereotypes and prejudices towards diverse ethnic groups, higher and lower status groups in the society are identified following their possibili- ties of power access. Results are analyzed in terms of social, cultural, cognitive and affective processes that mediate intergroup relations and result in social exclusion demonstrations. Finally, these results suggest that the institutionalization of exclusion practices is a culturalform of power perpetuation promoted by dominant groups.